For a metaphysics out of joint:: Deleuze, Heidegger: pathways between metaphysics and transcendental philosophy - Candiotto, Maurizio (Aoristo - International Journal of Phenomenology, Hermeneutics and Metaphysics, 2020)
In Heidegger the ontological difference is one between any intra-worldly entities and the very horizon of their appearing, the world itself. Both E. Fink and J.-P. Sartre elaborated on this, and so further did Deleuze; even his and Guattari’s Anti-Oedipus draws ultimately on the utterly Heideggerian idea of an ontological difference as one between world and worldly entities. Now the very architecture of traditional (Wolffian) special metaphysics – although programmatically entity-oriented – gets thereby affected, namely in its first part, rational psychology. From Heidegger through Fink and Sartre until Deleuze, the move of opening the metaphysical dimension of thought to the transcendental one in order to do justice to the ontological difference goes along with that of blowing psychology up (and indeed psyche itself) within the very domain of metaphysics.